Comparison of classifying the material mechanical properties by using k-Nearest Neighbor and Neural Network Backpropagation - Intan Maisarah, Abd Rahim; Fauziah, Mat; Sazali, Yaacob, Prof. Dr. (Science Academy, 2011)
Link to publisher's homepage at http://www.sciacademypublisher.com